FEASIBILITY STUDY OF FLOATING SOLAR POWER PLANTS IN SITU TUNGGILIS CILEUNGSI BOGOR REGENCY - Muliawati, Fithri; Annisa, Sarah Chairul; Wismiana, Evyta; Adzikri, Fikri; Waryani, Waryani (LPPM Univ. Ibn Khaldun Bogor, 2025)
Currently in Bogor City there are many potential areas that can be used as tourism locations. Tourist locations can also be a source of pride for local residents because they can improve the economy of local residents. By having distinctive cultural heritage characteristics, legendary historical stories to natural potential that has its own appeal, all have an important role in developing the economic welfare of the local community. Supporting factors that cannot be ignored are the infrastructure and comfort offered to support it as a tourist destination. Situ Tunggilis is one of 93 lakes in Bogor Regency, has good tourism potential, but the facilities and infrastructure in Situ Tunggilis are still less than optimal. One of the things that is still an obstacle is access to electrical energy. Therefore, access to electricity must be done immediately to increase the appeal and service to tourists. In meeting the main electricity needs in Situ Tunggilis, one of the efforts put forward is to utilize environmentally friendly New and Renewable Energy (EBT) sources, namely floating Solar Power Plants (PLTS). Based on this feasibility study, it can be concluded that solar energy obtained around Tunggilis can be used as an energy source for floating PLTS. Thus, this study can be applied as an effort to improve sustainable ecotourism facilities and infrastructure in Situ Tunggilis.